Mindful coaching : coaching the mental game for young athletes through connection - Beard, CG ([Place of publication not identifed] : [publisher not identified], 2022)
Mindfulness, cognitive flexibility, and overall mental game are often overlooked when it comes to youth coaching for any sport. However, these areas are vital to truly unlocking any young person's potential in the sporting arena. They say you need to "get your head in the game"--And no truer words have ever been spoken.
Introduction -- Part 1. Coaching Children -- Part 2. Finding Your Best Inner Coach -- Part 3. Mental Game 101 - For you and Your Athletes -- Conclusion -- Notes.
Mindful coaching :, Mindful
Keywords: SPORTS PSYCHOLOGICAL ASPECTS